The history of karate and the masters who made it development, lineages, and philosophies of traditional Okinawan and Japanese karate-do - Cramer, Mark I. (Berkeley, California Blue Snake Books, 2018)
"A concise yet comprehensive history of traditional Okinawan and Japanese karate, with biographies of the great karate masters This first concise yet comprehensive history of traditional Okinawan and Japanese karate includes authoritative biographies of the great karate masters of the past and the philosophical issues they faced as karate changed and evolved. Bringing a fresh understanding to the study of the martial arts, Mark I. Cramer dispels many of the often-repeated martial arts myths as he details the lineages of the modern styles of karate and describes the social, cultural, and political events that influenced them. While most books focus on a single style of karate or the biography of just one of the great teachers, this book offers a well-researched and detailed overview. By bringing all of this knowledge together in one volume, Cramer--who has trained and competed in karate for more than forty years, as well as won numerous awards and been inducted into the USA Karate Federation's Hall of Fame--fills a crucial gap"--
Includes bibliographical references and index.
Keywords: Karate -- Japan -- History; Martial artists -- Japan -- Biography; Martial artists -- Okinawa-ken -- Biography; Karate -- Japan -- Okinawa-ken -- History